Peran Lembaga Pemberdayaan Masyarakat Terhadap Peningkatan Ekonomi Masyarakat Terdampak Covid-19 Di Desa Bantarjaya Kabupaten Bogor - Sri Rahayu; Tantan Hermansah (UIN Siber Syekh Nurjati Cirebon, 2022)
The Covid-19 pandemic that has been going on since 2020 has disrupted economic life and welfare, including in rural communities in Indonesia. The Covid-19 pandemic not only has an impact on the economy but also affects the health, education, and social life of the Indonesian people. Therefore, the central and regional governments need to issue various policies to tackle the spread of Covid-19 as well as policies that are designed to mitigate the social and economic impacts of this pandemic. This disturbance also occurred and was felt by the community in Bantarjaya Village, Rancabungur District, Bogor Regency. The real form of the impact of Covid-19 on the economy is layoffs. Many employees were laid off and various companies were even threatened with bankruptcy. Not only that, many other aspects are affected, including freelance daily workers, MSME actors, and other businesses that involve a lot of people. Therefore, various parties are required to optimize various institutional potentials at the village level, such as the village Community Empowerment Institution (LPM). The purpose of the study was to analyze the role of knowing the role, constraints, and efforts of LPM in handling the economy and welfare of the people affected by the Covid-19 pandemic, as well as being a forum for handling and developing community empowerment, including dealing with communities affected by Covid-19. By using qualitative research methods, the results of the study show that the role of LPM in this context as a facilitator, mediator, dynamist, and motivator turned out to make a significant contribution to improving the welfare of the people in Bantarjaya Village, especially during the Covid-19 pandemic.